2021
DOI: 10.1021/acs.jmedchem.1c01215
|View full text |Cite
|
Sign up to set email alerts
|

Bioisosteres of the Phenyl Ring: Recent Strategic Applications in Lead Optimization and Drug Design

Abstract: The benzene moiety is the most prevalent ring system in marketed drugs, underscoring its historic popularity in drug design either as a pharmacophore or as a scaffold that projects pharmacophoric elements. However, introspective analyses of medicinal chemistry practices at the beginning of the 21st century highlighted the indiscriminate deployment of phenyl rings as an important contributor to the poor physicochemical properties of advanced molecules, which limited their prospects of being developed into effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
167
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(199 citation statements)
references
References 264 publications
(473 reference statements)
0
167
0
Order By: Relevance
“…[33] Cycloaliphatic rings can also serve as modest bioisosteric replacements of the phenyl ring, with the cyclobutane ring boasting improved physicochemical advantages over the cyclopentane and cyclohexane rings, respectively. [34] Another attractive application that the cyclobutane motif boasts is in the rigidification of acyclic propyl chains, such as in the case of the histamine H 3 receptor antagonists/inverse agonists [35] and retinoic acidrelated orphan receptor γt (RORγt) inverse agonists [36] -both cases in which an improved affinity was achieved. Additionally, the available carbocentric (carbon atom-based) growth vectors from the cyclobutane ring, which provide access to different molecular geometries, brand the motif particularly 'sociable.'…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33] Cycloaliphatic rings can also serve as modest bioisosteric replacements of the phenyl ring, with the cyclobutane ring boasting improved physicochemical advantages over the cyclopentane and cyclohexane rings, respectively. [34] Another attractive application that the cyclobutane motif boasts is in the rigidification of acyclic propyl chains, such as in the case of the histamine H 3 receptor antagonists/inverse agonists [35] and retinoic acidrelated orphan receptor γt (RORγt) inverse agonists [36] -both cases in which an improved affinity was achieved. Additionally, the available carbocentric (carbon atom-based) growth vectors from the cyclobutane ring, which provide access to different molecular geometries, brand the motif particularly 'sociable.'…”
Section: Introductionmentioning
confidence: 99%
“…A detailed comparison between the cyclobutane ring and various cycloaliphatic rings as well as 4‐membered heterocycles revealed that the cyclobutane ring compares favourably in terms of physicochemical properties and metabolic stability [33] . Cycloaliphatic rings can also serve as modest bioisosteric replacements of the phenyl ring, with the cyclobutane ring boasting improved physicochemical advantages over the cyclopentane and cyclohexane rings, respectively [34] . Another attractive application that the cyclobutane motif boasts is in the rigidification of acyclic propyl chains, such as in the case of the histamine H 3 receptor antagonists/inverse agonists [35] and retinoic acid‐ related orphan receptor γt (RORγt) inverse agonists [36] – both cases in which an improved affinity was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning pyridines ( Figure 2 ), they are one of the most prevalent examples of biologically active heterocycles, being the second most common ring in small molecule drugs. This is quite understandable since the pyridine ring is often used as an isosteric and/or bioisosteric replacer of phenyl rings [ 18 , 19 ]. There is only one example of a pyridine-fused BA compound [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…While BCHeps have been prepared by ring expansion of BCPs (20) and by cyclization of cyclohexane dicarboxylates (21), these approaches can be limited in substituent scope or involve lengthy synthetic sequences. We show that BCHeps can instead be conveniently and directly accessed from [3.1.1]propellane (1), a homologue of [1.1.1]propellane (2) which is widely used as the near-ubiquitous source of BCPs (22). We found 1 to be a versatile precursor that undergoes a variety of radical-based transformations to access a wide range of functionalized BCHeps, including drug analogues.…”
mentioning
confidence: 98%
“…Main Text: Strategies for the structural modification of lead molecules that improve pharmacokinetic properties and metabolic stability are increasingly sought in drug development (1). One example is the replacement of aromatic rings with non-classical bioisosteres such as small-ring cage hydrocarbons (2)(3)(4)(5). Such structures display a higher fraction of saturated carbon atoms compared to the parent arenes (Fsp 3 , corresponding to greater three-dimensionality), a property linked to greater clinical success rates (6).…”
mentioning
confidence: 99%